Phenotypic diversity for phenological and agronomic traits in the UC‐Riverside cowpea (Vigna unguiculata L. Walp) mini‐core collection. Issue 5 (1st July 2021) - Dareus, Rocheteau; Acharya, Janam P.; Paudel, Dev R.; Lopes De Souza, Cleber Henrique; Tome Gouveia, Beatriz; Chase, Carlene A.; DiGennaro, Peter; Mulvaney, Michael J.; Koenig, Rosalie; Rios, Esteban F.
Abstract: Cowpea ( Vigna unguiculata L. Walp) is a multipurpose crop widely cultivated in tropical and subtropical regions around the world. Characterizing cowpea phenotypes in germplasm collections is a crucial step to ensure future breeding efforts in the species. In this study, we estimated variance components and calculated genetic parameters for eight traits in 292 accessions from the University of California Riverside cowpea mini‐core collection, along with three lines released by the USDA, and seven cultivars. Broad‐sense heritability ( H 2 ) ranged from .21 to .83 for all accessions evaluated in Year 1, and from .16 to .83 for traits evaluated in 100 accessions during Year 2. Genotype × year correlations ranged from .45 to .99, illustrating consistency in phenotypic performance for some traits. Positive trait correlations were estimated for plant height and days to flowering, biomass at flowering (R1), and biomass at pod maturity (R6). Biomass at R1 and R6 were highly positively correlated. The USDA line US‐1137 showed high biomass production and can be used as forage and cover crop, whereas US‐1136, US 1138, and the cultivar Iron Clay showed superior traits as dual‐purpose (grain and/or fodder). Several accessions from the mini‐core outperformed cultivars and represent valuable genetic resources that can contribute to cowpea improvement. Moreover, these results showed that multiyear and/or multienvironment studies are needed to reliable select improved germplasm for agronomic traits. This study will provide cowpea breeders and geneticists with valuable phenotypic data to start new breeding efforts, and/or opportunities for gene discovery for key phenological and agronomic traits. Core Ideas: The UC‐Riverside mini‐core cowpea collection was phenotyped in Florida. Genetic parameters revealed large phenotypic diversity in this germplasm. Grain, forage, and multipurpose types were identified and selected. Accessions showed greater diversity than cowpea cultivars. The collection holds broad genetic diversity to improve cowpea productivity.